Digital Agricultural Services: The Future of Indian Farming - G. , Bhaskar (Journal of Agricultural Extension Management, 2022)
The advances in Information and Communication Technologies (ICTs) have shown the pathway to adopt digitisation in every aspect, in the services offered by both National and State Governments. The Agricultural sector is also taking a lead to bring huge changes in the utilisation of ICTs in agriculture. The Government of India has initiated a Mission Mode Project in Agriculture to develop ICT enabled services for farmers through a number of services that help the farmers in day-to-day activities. Further, the Digital Agricultural Mission focuses on using emerging technologies like Internet of Things (IoT), Robotics, Kisan Drones, Artificial Intelligence (AI), Machine Learning (ML), Blockchain technologies, Remote Sensing etc. These emerging digital agriculture services will enhance the farming activity and also provide better financial benefits. This paper discusses various digital agricultural services to strengthen the agricultural extension system